What does transverse furrow train in scabland-like topography originate from? The unique records of upper-flow-regime bedforms of a glacial lake-outburst flood in NE Poland. (20th April 2022) - Weckwerth, Piotr; Kalińska, Edyta; Wysota, Wojciech; Krawiec, Arkadiusz; Adamczyk, Aleksander; Chabowski, Marek
Abstract: High-energetic glacial lake-outburst floods are known both from ancient and current glacial environments. While a decrease in meltwater flow energy takes place, a proglacial bedform continuum is formed due to erosional and depositional processes; these have been studied in relatively little detail as compared to the sediment transport modes and deposition processes of glacial lake-outburst floods. Therefore, we consider upper-flow-regime bedforms that originate from glacial lake-outburst floods under subaerial conditions in the ice-proximal portion of floodwater spillways as the main interest of this study, and we particularly focus on a suite of features of scabland-like topography in NE Poland. A Digital Elevation Model (DEM) is used to detect the relevant landforms and to provide their morphometric parameters, and is further combined with sediment lithofacies analysis. These methods allow us to recognise a train of transverse furrows that consists of seven main and two associated depressions that altogether constitute a longitudinal cluster interpreted as cyclic steps. These bedforms developed due to (1) upstream progradation of troughs with gravelly lags, (2) scour infill with backset and foreset facies in hydraulic jump zones and (3) sedimentation on the downflow side of hydraulic jumps. The recognised cyclic steps reveal their transportational type with five scour-and-fill events under conditions of high sediment concentration and low bed resistance to floodwater erosion. Later, transverse furrows experienced aeolian accumulation and mass wasting that both made them shallower.